Respuesta :

Answer:

[tex] \orange { \bold{a = \frac{c \sqrt{b} }{(1 - \sqrt{b}) } }}[/tex]

Step-by-step explanation:

[tex]b = \frac{ {a}^{2} }{ {(a + c)}^{2} } \\ \\ b = \bigg(\frac{ {a} }{ {a + c}} \bigg)^{2} \\ \\ \sqrt{b} = \frac{a}{a + c} \\ \\ (a + c) \sqrt{b} = a \\ \\ a \sqrt{b} + c \sqrt{b} = a \\ \\ a \sqrt{b} - a = - c \sqrt{b} \\ \\ a( \sqrt{b} - 1) = - c \sqrt{b} \\ \\ a = \frac{ - c \sqrt{b} }{( \sqrt{b} - 1)} \\ \\ \purple{ \bold{a = \frac{c \sqrt{b} }{(1 - \sqrt{b}) } }}[/tex]